The role of servant leadership in improving the performance of the Education Department in Bisha Governorate, Kingdom of Saudi Arabia - AlHarthy, Abdullah Saeed Salim (Journal of Economic, Administrative and Legal Sciences, 2022)
This study aimed to identify the reality of the relationship between servant leadership and performance improvement in the Education Department in Bisha Governorate. To achieve the objectives of the research, the researcher used the descriptive approach, The study reached a set of results, the most important of which are: that the reality of servant leadership in the Education Department in Bisha Governorate came to a high degree, and the reality of performance in the Education Department in Bisha Governorate came to a medium degree, and that the relationship between servant leadership and performance improvement in the Education Department in Bisha Governorate was medium.The study recommended the necessity of the director’s interest in the Education Department to put the staff’s vision within the goals and objectives of the organization in the Bisha governorate, and to follow fair procedures in dealing with workers, develop workers’ skills according to modern scientific methods, and encourage the presentation of innovative and new ideas to improve administrative work in Bisha governorate.